PENGEMBANGAN WAHANA UKUR KECEPATAN ARUS ALIRAN SUNGAI - Martinus Martinus; Ahmad Suudi; Rahmat Dendi Putra; Meizano Ardi Muhammad (BAROMETER, 2020)
The river has potential as a power plant with indicators in the form of river flow. Flowmeter is a measuring tool used to determine of the flow.Conventional flowmeters have limited use in a wide and deep coverage area. So it was designed a new measurement vehicle for rapid movement in waters that were difficult to reach. A GPS is used to help the accuracy of the measurement location so that data is realtime. This research was conducted by developing a measurement vehicle in the form of a ship. This vehicle had a length of 84 cm, a width of 25,5 cm, and a height of 11 cm. This measuring vehicle has a flowmeter and GPS that are controlled using Arduino. The measuring vehicle has 3 stages of manufacture in the form of physical design, control design, and assembly. Field testing is done by crossing 5 points of reference that have been. The test was carried out with 3 times the data collection on 3 sides of the river. The result of this test was the floating vehicle could measure current speed with high mobility in realtime data. One of the result of water flow measurement on the flowmeter is 430.98 cm/s with error probability 12,6%.